Analisis Pengaruh Kualitas Pelayanan, Brand Image dan Fasilitas terhadap Kepuasan Konsumen (Studi Kasus pada Angkutan Feeder 1 Trans Semarang) - Satrya, Rafi Nanda; Yuliati, Yuliati; Wahyuningsih, Susanti; Indriyatni, Lies; Widodo, Untung (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
This study aims to determine the effect of Service Quality, Brand Image and Facilities on Consumer Satisfaction using the Trans Semarang feeder 1 transportation service. The research population is all consumers of Feeder 1 Trans Semarang, a sample of 100 uses the Ferdinand formula. The method used is multiple linear regression SPSS program version 23. Multiple linear regression analysis technique Y = α + β1X1 + β2X2 + β3X3 + e. The research data variable is Consumer Satisfaction (Y) and X is Service Quality, Brand Image and Facilities. The results of the Service Quality study (X1) have no significant effect on consumer satisfaction with t count t table (3.161>1.984), with a significance value of 0.002 t table (3.930>1.984), with a significance value of 0.000 F table (120.22> 2.699) with a significance of 0.000. Calculation of the value of the Coefficient of Determination (R2) obtained Adjusted R2 of 0.783. This means that the percentage of the influence of the variable Quality of Service, Brand Image and Facilities on Customer Satisfaction is 78.3%. Keywords: Service Quality, Brand Image, Facilities and Customer Satisfaction.